Some researchers wear yellow pants, but even fewer participants read consent forms: Exploring and improving consent form reading in human subjects research - Douglas, Benjamin D; McGorray, Emma L; Ewell, Patrick J (Psychological methods, 2021)
Though consent forms include important information, those experienced with behavioral research often observe that participants do not carefully read consent forms. Three studies examined participants' reading of consent forms for in-person experiments. In each study, we inserted the phrase "some researchers wear yellow pants" into sections of the consent form and measured participants' reading of the form by testing their recall of the color yellow. In Study 1, we found that the majority of participants did not read consent forms thoroughly. This suggests that overall, participants sign consent forms that they have not read, confirming what has been observed anecdotally and documented in other research domains. Study 2 examined which sections of consent forms participants read and found that participants were more likely to read the first 2 sections of a consent form (procedure and risks) than later sections (benefits and anonymity and confidentiality). Given that rates of recall of the target phrase were under 70% even when the sentence was inserted into earlier sections of the form, we explored ways to improve participant reading in Study 3. Theorizing that the presence of a researcher may influence participants' retention of the form, we assigned participants to read the form with or without a researcher present. Results indicated that removing the researcher from the room while participants read the consent form decreased recall of the target phrase. Implications of these results and suggestions for future researchers are discussed. (PsycInfo Database Record (c) 2021 APA, all rights reserved).